Assessing the internal structure of landslide dams subject to possible piping erosion by means of microtremor chain array and self-potential surveys - Wang, Fawu; Okeke, Austin Chukwueloka-Udechukwu; Kogure, Tetsuya; Sakai, Tetsuya; Hayashi, Hisao (Engineering geology, 2018)
An integrated geophysical approach comprising microtremor chain array and self-potential surveys was used to assess the internal structure of landslide dams subject to possible piping erosion in selected sites in Japan and Kyrgyzstan. The non-invasive geophysical approach is cost effective, environmentally friendly and portable, and hence, it has proven to be valuable for the geotechnical assessment of landslide dams where piping can trigger failure of the dam. While the microtremor chain array survey results revealed the internal structure of the landslide dam, the self-potential survey results indicated the path of anomalous seepage zones. In the surveyed sites of long-existing landslide dams, the presence of a seepage path in the dam was confirmed by a good correlation between the areas of low phase velocity and large negative self-potential anomalies. In summary, this integrated geophysical approach could be useful for the early risk assessment of landslide dams and prediction of landslide dam failure by piping. •A microtremor chain array survey was successfully used to detect the internal structure of landslide dams.•Self-potential surveys are useful for detecting the seepage route in a landslide dam.•The integration of the two surveys could be useful in evaluating landslide dams’ susceptibility to failure.